(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
In this article we have studied a drafting of a chain of successive superpositions of some pairs of points for modeling of a curve as a part of the frame of a curvilinear surface. It was shown that a superposition of n points of the discrete analog of a given curve can be replaced by a chain of successive superpositions. Also we have got formulas for calculating superposition coefficients of the chain, which allow determining coordinates of unknown nodal points of the curve without making any system of equations.